ECOLOGY VIS-À-VIS HUMAN ECOLOGY - Porathur, Lijo (Journal of Dharma, 2014)
Ecology is one of the important concerns of this age. Pope Benedict XVI who is often called ‘the Green Pope’ was the voice of Church in this concern. Through his encyclicals, messages and talks Pope Benedict XVI dwelt on the problem of human responsibility towards nature. The ecology of Pope Benedict XVI, which is rooted in the biblical vision of nature, proclaims that the earth is a gift of God to human beings, a home to live in, with a responsible stewardship. He stands for a human-centred ecological view. For him natural ecology is important, but human ecology is first. The book of ‘nature’ is one and indivisible: it takes in not only the environment but also life, sexuality, marriage, the family, social relations: in a word, integral human development. When ‘human ecology’ is respected within the society, environmental ecology also benefits. This article sheds light on the two key concepts that the humankind is greater than nature and nature is not a raw material to be manipulated. Human beings and nature are interdependent; the weakening of one, places other at risk.